Nutrição, produção e biofortificação agronômica com zinco em cultivares de feijoeiro-comum - Kachinski, Wagner Deckij (2019)
Deficiency of zinc (Zn) affects billions of people worldwide. The objective of this study was to evaluate the effect of the soil and foliar application of Zn on plant nutrition, yield, grain nutritional quality and biofortification, and nutrient export as a function of Zn fertilization in common bean (Phaseolus vulgaris L.) under no-till system in an oxisol of the South region of Brazil. Two consecutive summer harvests (2016/17 and 2017/18 harvests) were carried out and two common bean cultivars were used: BRS Esteio (black bean) and IPR Campos Gerais (Carioca bean). In 2016/17 harvest year, treatments were composed of foliar applications of Zn doses at the stage of grain filling with the cultivar BRS Esteio, and in 2017/18 harvest year the treatments were both soil and foliar Zn application at different phenological stages with the cultivars BRS Esteio and IPR Campos Gerais. Soil and foliar Zn applications during the flowering period increased the insertion height of the first pod in cultivar BRS Esteio, but there was no effect on cultivar IPR Campos Gerais. Foliar Zn spraying at the flowering time (phenological stage R6) increased leaf Zn content by approximately two times in both common bean cultivars, but negatively affected the grain yield in cultivar BRS Esteio. Nonetheless, foliar Zn application during the initial and final stages of grain filling (phenological stage R8) did not influence the grain yield in both cultivars. In treatments without both soil and foliar Zn application, the descending order of nutrient export from the field was as follows: N > K > P > Ca ≈ S > Mg for macronutrients and Fe > Mn > Cu > Zn for micronutrients. Foliar Zn spray increased the Zn, P, Ca, Mg, S, Mn, Cu and Fe exports in grains of the cultivar IPR Campos Gerais, while soil Zn application resulted in higher P, K and Mn exports in grains of the cultivar BRS Esteio. Both soil and foliar Zn application considerably increased the grain Zn content in cultivar BRS Esteio, however, in cultivar IPR Campos Gerais there was only effect of the foliar Zn application. Single leaf spray of 600 g ha-1 of Zn at the initial grain filling stage was shown to be the best way to improve the grain Zn content. Foliar Zn spray at the final stage of grain filling favored the increase of pod Zn content in detriment of grain Zn content. The soil Zn application increased the concentrations of total amino acids and proteins (albumins, globulins and prolamins) in the bean grains, thus improving nutritional quality.